Kala Farms a dairy carabao agritourism resort - Domingo, Venson John R.
This thesis is a proposal for a dairy carabao agritourism resort, to promote the carabao milk as a food commodity as well as to provide small-hold farmers a support center. The development includes buildings such as the carabao farm, milk processing plant and tourist villas, supported by tourist center, administration building and training center. The process starts with preliminary research and an analysis of present conditions. The gathered information would be used as basis for the making of the architectural program. After going through a comprehensive and cyclical design process, the compiled work is then presented in a thesis deliberation before a panel of jurors. The resultant design showcased here uses the concept of architecture of harmonious contrast that instills a sense of sacredness through subdued ceremonial spaces. The contrast between the formal architecture and the organic nature. It uses contrast of formal architecture and organic landscape to stress importance in promoting the carabao milk as a food commodity. Using the concept of agritourism as a medium to integrate tourism, education, and productivity to create a facility for small-hold farmers.